Technically involved : technology-based youth participation activities for your library - Braun, Linda W. (American Library Association, 2003)
Here are practical measures to transform your library with teen power. Author and YA/ technology advocate Linda Braun outlines some proven ideas to invite participation and channel teen interest in technology, giving teens an opportunity to serve their community. Braun advocates working with teens to create library technology-related projects for themselves and others. Technically Involved offers ready-made training and skills checklists, as well as examples of successful youth participation activities, to inspire librarians and teens as they start out and help them determine what they need to know. Project ideas include online storytelling, tutorial design and tours, e-mail newsletters, literacy programming, and intergenerational programs. Filled with success stories, examples, and a wealth of potential teen-library technology programs, Technically Involved gives librarians a proactive toolkit for harnessing teen energy with technology for the library.